CONCEPTUAL UNDERSTANDING TEST INSTRUMENT ON ELECTRIC FORCE AND FIELD MATERIAL - Afrizah, Tasya; Suhadi, Suhadi; Mabruroh, Faizatul; Putri, Jamiatul Khairunnisa (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to develop a test instrument for understanding concepts on the material of force and electric field that meets the qualifications including aspects of validity and reliability. This study is a development with the ADDIE approach which stands for Analysis, design, development, implementation, and evaluation. This study was conducted at SMA Negeri 1 Banyuasin III with a sample of 30 students in class XII.3. The test instrument was declared feasible based on expert validation tests, the level of validity of the question items and reliability tests. Based on the research that has been done, the average score from the expert validation test was 3.64 which indicates a feasible category. At the level of validity of the tested question instrument if r-count > r-table then the question is declared valid. The r-table value used was 0.3610, in this test instrument there were 10 questions that were declared valid, with a range of r-count values of 0.3697 to 0.5362. In the reliability test, this instrument was declared reliable with a reliability value of 0.65.